Potential role of the Eph/ephrin system in colorectal cancer: emerging druggable molecular targets - Scarini, João Figueira; Gonçalves, Moisés Willian Aparecido; de Lima-Souza, Reydson Alcides; Lavareze, Luccas; de Carvalho Kimura, Talita; Yang, Ching-Chu; Altemani, Albina; Mariano, Fernanda Viviane; Soares, Heloisa Prado; Fillmore, Gary Chris; Egal, Erika Said Abu (Frontiers in Oncology, 2024)
The Eph/ephrin system regulates many developmental processes and adult tissue homeostasis. In colorectal cancer (CRC), it is involved in different processes including tumorigenesis, tumor angiogenesis, metastasis development, and cancer stem cell regeneration. However, conflicting data regarding Eph receptors in CRC, especially in its putative role as an oncogene or a suppressor gene, make the precise role of Eph-ephrin interaction confusing in CRC development. In this review, we provide an overview of the literature and highlight evidence that collaborates with these ambiguous roles of the Eph/ephrin system in CRC, as well as the molecular findings that represent promising therapeutic targets.